2020
DOI: 10.1002/hed.26183
|View full text |Cite
|
Sign up to set email alerts
|

Commentary on the management of total laryngectomy patients during the COVID‐19 pandemic

Abstract: The coronavirus disease-2019 (COVID-19) pandemic has rapidly spread across the world, placing unprecedented strain on the health care system. Health care resources including hospital beds, ICUs, as well as personal protective equipment are becoming increasingly rationed and scare commodities. In this environment, the laryngectomee (patient having previously undergone a total laryngectomy) continues to represent a unique patient with unique needs.Given their surgically altered airway, they pose a challenge to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
110
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(121 citation statements)
references
References 21 publications
6
110
0
1
Order By: Relevance
“…36 Alternatives, such as CT, ultrasound, and X-ray, should be considered for other cases, depending on the diagnostic hypothesis. 22,36 An aspect of remarkable relevance is the PPE that should be used. Chan et al published the Hong Kong recommendations regarding PPE use.…”
Section: Endoscopic Examinationsmentioning
confidence: 99%
“…36 Alternatives, such as CT, ultrasound, and X-ray, should be considered for other cases, depending on the diagnostic hypothesis. 22,36 An aspect of remarkable relevance is the PPE that should be used. Chan et al published the Hong Kong recommendations regarding PPE use.…”
Section: Endoscopic Examinationsmentioning
confidence: 99%
“…These published papers and web-based statements contain precise recommendations for the performance of certain surgical procedures (e.g., tracheostomies) [9][10][11][12][13][14][15][16][17]. Others provide general protection advice for ORLs [18][19][20][21][22][23][24][25][26][27] or similarly atrisk disciplines [28,29]. Out of an abundance of caution, some otorhinolaryngological procedures like anterior rhinoscopy or the use of rigid or flexible endoscopes [30][31][32][33] were advised to be avoided unless absolutely necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Study characteristics are summarized in Table 1. 3,[19][20][21][22] When searching the websites of professional organizations, we found that 3 had produced relevant guidance documents. [13][14][15] Following data extraction and synthesis, the results were categorized according to practice domains for tracheostomy and laryngectomy.…”
Section: Results and Observationsmentioning
confidence: 99%
“…The main recommendations according to each practice area are shown in Table 2. 3,13,14,[19][20][21][22][23][24][25]…”
Section: Results and Observationsmentioning
confidence: 99%
See 1 more Smart Citation